NO Binding to Cobalamin: Influence of the Metal Oxidation State - van Eldik, Rudi; Clark, Timothy; et al. (Inorganic Chemistry, 2004)
Density functional and molecular orbital theory calculations on models for cobalamin suggest that NO binds similarly to the Co(II) and Co(III) oxidation states. However, Co(III) can bind water far more strongly than Co(II) as a sixth ligand, so that the competition between water and NO complexation strongly favors water for Co(III) in the gas phase. Although the Co(II) oxidation state is found to bind water slightly more strongly than NO in the gas phase, the inclusion of solvation effects via the polarizeable continuum model makes NO binding more favorable. Thus, the experimentally observed ability of cob(II)alamin to bind NO in aqueous solution is the result of its weak complexation with water and the relatively poor solvation of NO. Calculated vibrational frequencies support the interpretation of the cob(II)alamin-NO complex as being cob(III)alamin-NO-, although the DFT calculations underestimate the degree of charge transfer in comparison to Hartree-Fock calculations.
UnivIS-Import:2015-03-09:Pub.2004.forsch.sonder.sfb583.nobind